Modern and Convensional Wound Dressing to Interleukin 1 and Interleukin 6 in Diabetic wound - Werna Nontji; Suni Hariati; Rosyidah Arafat (Universitas Airlangga, 2015)
Introduction: Holistic wound care is one of the ways to prevent gangrene and amputation, modern wound dressing is more effective than convensional with increasing transforming growth factor and cytokine, especially interleukin. This study aims to identify the effectiveness of Modern and Convensional Wound Dressing to Interleukin 1 (IL-1) and Interleukin 6 (IL-6) in Diabetic wound.Methods:A Quasi eksperimental pre-post with control group design was used. The intervention given was modern wound dressing and Control group by convensional wound dressing, This study was conducted in Makassar with 32 samples (16 in intervention group and 16 in control group). Results: The result of Pooled T- test showed that p = 0.00 (p < 0.05), it means that there was signifi cant correlation between modern wound dressing to IL-6 and IL-1 than Convensional wound dressing. Conclusion: Process of wound healing was produced growth factor and cytokine (IL-1 and IL-6), it will stimulated by wound dressing, modern wound dressing (Calcium alginat) can absorb wound drainage, non oklusive, non adhesif, and autolytic debridement.